Integrating Indragiri Hulu Local Wisdom into Audiovisual Math Module for Elementary Education - Yusmia Rika Subekti; Herlinawati Herlinawati; Yogi Yunefri (AL-ISHLAH: Jurnal Pendidikan, 2024)
This study aimed to evaluate the effect of local wisdom-based audiovisual modules on improving learning outcomes in mathematics among second-grade students at YMI Tani Makmur Elementary School. The research employed a purposive sampling method to select students studying two- and three-dimensional shapes, aligning with the developed module. The study involved designing the module, validating it through expert reviews, and assessing student responses. Validation was conducted by teaching material experts (focusing on content and evaluation) and media experts (focusing on design, interactivity, and communicativeness). Expert validation results indicated an average score of 72.3% from material experts, categorized as "valid," and 94.4% from media experts, categorized as "very valid." These results confirmed that the module meets the validity criteria for audiovisual instructional materials. Observations during implementation revealed that educators found the module helpful in enhancing students’ learning outcomes and motivation in mathematics. The findings demonstrate the potential of local wisdom-based audiovisual modules to make mathematics learning more engaging and effective for elementary school students. The study concludes that the validated module is a valuable tool for improving both motivation and academic performance in mathematics, supporting its use in elementary education settings. Further research could explore its application across different subjects and grade levels.